Exploring teacher cognition in Malaysian ESL classrooms - Bromeley Philip,; Tan, Kim Hua; Willie Jandar, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The paper addresses the key question in teaching English language, that is, how does teacher cognition interact with classroom practice. The paper is part of a larger study which was conducted in sub-urban schools in Sarawak, East Malaysia via qualitative case study method involving teachers in actual classroom practice. The teacher participants were video-recorded in two separate teaching sessions to capture as far as possible authentic teacher cognition practice. Each teacher was then asked to review his own recorded lessons and verbally report on his actions in the class via stimulated recall protocol technique. The qualitative data generated were analysed for specific features in relation to three main knowledge types representing teacher cognition namely, knowledge of students, pedagogical content knowledge and general pedagogical knowledge. Several features were identified and categorised according to the knowledge types. As far as Knowledge of students (KS) is concerned, it is important for teachers to be aware of their students’ preferred learning styles as well as their proficiency levels. On Pedagogical Content Knowledge (PCK), teachers should allow their students a lot of freedom in choosing the activities they prefer. As regards General pedagogical knowledge (GPK), teachers need to be less dominating in the actual classroom practice but instead acting more as facilitator to help guide and facilitate the students’ learning process. For future research, it is recommended that longitudinal studies be conducted to further provide insights into teacher cognition via generation of larger corpus of data on evidence of teacher cognition processes.